Process Optimization and CO2 Emission Analysis of Coal/Biomass Gasification Integrated with a Chemical Looping Process - Ratikorn Sornumpol; Dang Saebea; Amornchai Arpornwichanop; Yaneeporn Patcharavorachot (Energies, 2023)
Biomass gasification is an attractive technology and one of the pathways for producing hydrogen. Due to the variable seasons and low calorific value of biomass, the addition of coal in the gasifier is suggested because coal has a high calorific value and carbon-to-hydrogen ratio. In general, the gaseous product obtained in gasification always contains a high amount of carbon dioxide, therefore, the co-gasification of biomass and coal should integrate with the calcium looping carbon dioxide capture process to provide purified hydrogen. In this work, the model of the co-gasification of biomass and coal integrated with the calcium looping carbon dioxide capture process was developed through an Aspen Plus simulator. The developed model was used to analyze the performance of this process. The sensitivity analysis demonstrated that increasing the gasification temperature, steam-to-feed (S/F) ratio, calcium oxide-to-feed (CaO/F) ratio, and regenerator temperature could improve hydrogen production. Next, further optimization was performed to identify the optimal operating condition that maximizes hydrogen production. The results showed that the optimal operating temperature of the gasifier is 700 °C with an S/F mass ratio of 2 and coal to biomass (C/B) mass ratio of 0.75:0.25. However, the carbonator and regenerator temperatures should be 450 °C and 950 °C, respectively, with a CaO/F mass ratio of 3. Under these operating conditions, the maximum H2 content and H2 yield can be provided as 99.59%vol. (dry basis) and 92.38 g hydrogen/kg biomass feeding. The other results revealed that the energy efficiency and carbon capture efficiency of this process are 42.86% and 99.99%, respectively, and that the specific emission of released CO2 is 80.77 g CO2/MJ.
Keywords: Chemical Looping and Thermochemical Processes; Thermochemical Biomass Conversion Processes; Carbon Dioxide Capture Technologies